TERAPI AKUPUNKTUR DAN POLA HIDUP SEHAT UNTUK MENURUNKAN TEKANAN DARAH PADA PENDERITA HIPERTENSI - Maria Dewi Christiyawati; Purwanto Purwanto (Poltekkes Kemenkes Surakarta, 2021)
Background: Hypertension is a disease that is a public health problem found in both developed and developing countries. It takes obedience and discipline and money to be able to control high blood pressure. Acupuncture can be applied to help control blood pressure by stimulating acupuncture points to deliver and smooth the Qi in an effort to balance Yin Yang which medically can improve the physiology of blood pressure. More than 20% of the Bibis Luhur RW XXI Nusukan Banjarsari Surakarta community complained of frequent dizziness and experiencing high blood pressure. Methods: Examination of blood pressure checks, counseling on healthy lifestyles and prevention of hypertension, as well as acupuncture therapy services located at Griya Sehat Prima Hati. The activity was carried out 12 times with a frequency of once a week with local health cadres. Blood pressure was checked at each visit and blood pressure comparisons were made from the first and last therapy. Results: There was an average decrease of 19 mmHg for systolic pressure and 10 mmHg for diastolic pressure. Patients, families and health cadres experienced an increase in knowledge about hypertension management and a healthy lifestyle by 80%. Acupuncture reduces comorbidities for people with hypertension such as dizziness, insomnia, stiff neck, and other complaints. Conclusion: With counseling, health care, and acupuncture therapy to help people understand and improve their daily life patterns, reduce complaints, and lower blood pressure.